(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The use of water resources for agricultural purposes, Agricultural water resource, main body of regional water resources, was affected by multiple factors (e.g. landform, climate, precipitation and water system). The water requirement will vary depending upon the crop cultivated in that area. The controller considers different parameters such as types of crop in that area, temperature, humidity, and wind speed while estimating the requirement of water. A case study shows that the optimal irrigation schedule can achieve water saving and production increment compared with the conventional irrigation schedule in which the whole field is fully irrigated. These measures mentioned above optimize disposition of agricultural water resources after the earthquake via source, transportation, irrigation, conservation and use of agricultural waters. Additionally, they could increase efficiency of utilization, reduce negative impacts to environments, and ensure durative of agricultural production.